Comparison of two methodologies to measure agricultural occupational fatalities. - Murphy, D J (1990)
Agricultural occupational fatalities in Pennsylvania for the years 1985-87 were followed up. Supplemental data concerning the occupation of the deceased and circumstances of the fatal accident were obtained from a family member. The number of fatalities designated as agriculturally and occupationally related by the National Traumatic Occupational Fatality (NTOF) system was compared with the number of fatalities identified by using alternative criteria for classification of agriculturally and occupationally related fatalities. There may be nearly a 30 percent error in the NTOF method resulting in a 20 percent undercount.